Pengaruh Ekstrak Daun Mimba (Azadirachta indica) terhadap Histamin Daging Ikan Tongkol Abu: The Effectiviness of Neem Leaves (Azadirachta indica) to Longtail Tuna Meat Histamine - Witria, Witria; Zainuri, Muhammad (Jurnal Pengolahan Hasil Perikanan Indonesia, 2021)
Longtail tuna (Thunnus tonggol) as scrombidae family which has high histamine contain that can cause poisoning for consumers. Some attempts can decrease histamine contain, one of them are use mimba leaves (Azadirachta indica). The research aimed to determine the effectiveness of neem leaves extract giving towards tongkol fish histamine. Neem leaves extraction use maceration method as long as 2 days. Longtail tuna sampel that measured of length is 30 cm which kept on room temperature as long as 5 hours used as sample research. The used treatment was immersion of neem leaves extract with concentration 5%, 25%, and 50%. Histamine analysis use HPLC device and data tabulation with SPSS program. The research result show the histamine contain of control treatment, 5%; 25%; and 50% respectively was 60.03, 49.63, 50.54, and 53.81 ppm. SPSS test results has indicate that giving of 5% neem leaves extract concentration to tongkol fish is more effective to prevent the increasing of tongkol fish histamine contain. Neem leaves extract concentration which 5%, 25%, and 50% respectively can decrease longtail tuna fish histamine contain with the effectiviness value was 17.15%, 15.80%, and 10.36%.